KETAKUTAN TERHADAP KEMATIAN DITINJAU DARI KEBIJAKSANAAN DAN ORIENTASI RELIGIUS PADA PERIODE REMAJA AKHIR YANG BERSTATUS MAHASISWA - Wahyu Wicaksono; Sito Meiyanto (Jurnal Psikologi, 2003)
This research was aimed to examine the correlation between wisdom and religious orientation with fear of death among late adolescence college students. Three hypotheses were tested: (a) there was a negative correlation between wisdom and fear of death, (b) there was a negative correlation between intrinsic religious orientation and fear of death, (c) there was a positive correlation between extrinsic religious orientation and fear of death. The Subjects of this research were 158 undergraduate (S-1) students at Department of Psychology, Gadjah Mada University. The range of age was between 17-22 years old. The regression analysis was used to examine. The results showed that (a) there was a negative and significant correlation between wisdom and fear of death r = -0.209, sig. 0.004, partial correlation -0.226, (b) there was a negative correlation between intrinsic religious orientation and fear of death r =-0.037, sig. 0.323, partial correlation -0.175, (c) there was a positive and significant correlation between extrinsic religious orientation and fear of death r = 0.285, sig. 0.000, partial correlation 0.350. r=0.401, adjusted R2 = 0.145, sig.0.000. Keywords: Fear of death, Death fear, Death anxiety, Wisdom, Intrinsic extrinsic religious orientation.